Pengaruh Religiositas terhadap Minat Mahasiswa Menabung di Bank Syariah - Peni Darmisah; Saiin Saiin (STAI Auliaurrasyidin Tembilahan, 2021)
As students who have an educational background in Islamic Economics, each has a different perception of Islamic Banking. There are still students who compare Islamic banks and conventional banks, a doubt toward the operational saving system, financing or discounting, and the existence of conventional Banks being more affordable than Islamic banks in remote areas. This study aimed to examine the effect of religiosity on students' interest in saving in Islamic banks. This type of research was quantitative with data analysis using a simple regression method. The results showed that the t count was 14,832, and the t table was 1,975 < t count 14,832 with a significance of 0.000 under 0.05. Therefore, it concluded that religiosity significantly affects the saving interest of students at Islamic Banks.